Multidisciplinary Tiered Care Is Effective for Children and Adolescents With Rumination Syndrome. Issue 3 (11th October 2022) - Sabella, Julia; Kroon Van Diest, Ashley M.; Bali, Neetu; Vaz, Karla; Yacob, Desale; Di Lorenzo, Carlo; Lu, Peter L.
Abstract : Objectives: Rumination syndrome (RS) can be challenging to treat and data on treatment outcomes in children are limited. The objective of this study was to evaluate outcomes of children with RS treated with tailored outpatient and inpatient strategies. Methods: We performed a retrospective cohort study of children <18 years old with RS evaluated at our institution from 2018 to 2020. At our institution, we use a multidisciplinary, tiered approach to treatment based on presentation severity. Children with RS either undergo outpatient treatment program (OP) or participate in an intensive outpatient program (IOP) or an intensive inpatient program (IP). We reviewed baseline characteristics and assessed severity (including frequency of regurgitation/vomiting, route of nutrition, and weight loss) at baseline, at completion of treatment, and at a follow-up time point. Results: We included 171 children with RS (64% female, median age 13 years, interquartile range (IQR) 10–15), 123 of whom had post-treatment data after completing OP, IOP, or IP. At baseline, 66% of patients were vomiting daily and 40% were losing weight. After treatment, 72% of OP, 95% of IOP, and 96% of IP patients reported that symptoms were better or fully resolved compared to baseline. In all 3 treatment groups, patients were vomiting, losing weight, and skipping meals significantly less after treatment compared to baseline. At follow-up (median 5.3 months), 86% of IOP and 66% of IP patients had symptoms that remained better or resolved. Conclusions: RS can cause severe symptoms, impacting nutritional status and school participation. However, multidisciplinary care in a tiered approach leads to significant symptomatic improvement. Abstract :